Phytochemical Study, Cytotoxicity, and Genotoxicity of the Methanolic Extract of Geranium diffusum Kunth - Juan Carlos Romero-Benavides; Tatiana Añazco-Loayza; Anabel Correa-Sinche; Andrea Alvarez-Ruiz; Luis Miguel Guamán-Ortiz; Rodrigo Duarte-Casar; Natalia Bailon-Moscoso (Plants)
Geranium diffusum Kunth is a medicinal plant native to Ecuadorian highlands with limited scientific study despite its ethnopharmacological relevance. The present study investigates the phytochemical properties and cytotoxic effects of the methanolic extract of G. diffusum. Comprehensive analyses revealed a rich composition of bioactive compounds, predominantly flavonoids and rutin, isoquercetin, and isorhamnetin-3-glucoside, known for their therapeutic potential, were isolated. The extract and its solvent fractions were evaluated for cytotoxic activity against three cell lines: RKO, SW613-B3, and HCT-116. Notably, the ethyl acetate fraction exhibited cytotoxicity with an IC50 value of 44.47 ± 1.02 μg/mL against the SW613-B3 cell line, indicating its significant anticancer activity. The dichloromethane fraction also demonstrated noteworthy effects on the RKO and HCT-116 lines, while the methanolic fraction exhibited higher viability in HCT-116 cells. No genotoxicity was found in CHO-K1 cells. These findings underscore the potential of Geranium diffusum as a valuable source of bioactive compounds for developing therapeutic agents against cancer and highlight the need for further research into its pharmacokinetics, in vivo efficacy, and the synergistic effects of its flavonoid constituents. This study contributes to enhancing our understanding of underexplored medicinal plants and supports conservation efforts for Ecuadorian biodiversity.